PENGUATAN LITERASI DIGITAL DALAM MENDUKUNG TRANSFORMASI DESA MENUJU SMART VILLAGE - Qalbi, Nur; Mallapiang, Yasser; Rahman, Abd Rahman (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
Digital transformation presents both a challenge and an opportunity in rural development. This community service program (PKM) aims to enhance the digital knowledge and skills of residents in Kalenna Bontongape Village, Takalar Regency. The activities included training sessions, outreach, and simulations based on digital applications. A participatory method with an educative-applicative approach was employed. The results showed significant improvements in the use of digital applications, understanding of the Smart Village concept, and the emergence of self-directed learning initiatives. The main challenges involved limited infrastructure, a lack of local facilitators, and low initial digital literacy. Key recommendations include the provision of digital learning facilities, tiered training programs, and multi-stakeholder collaboration. These findings highlight the importance of sustainable and adaptive strategies in fostering inclusive and competitive digital villages.